"Electro‐Typing" on a Carbon‐Nanoparticles‐Filled Polymeric Film using Conducting Atomic Force Microscopy. Issue 47 (2nd November 2017) - Goswami, Sumita; Nandy, Suman; Banerjee, Arghya Narayan; Kiazadeh, Asal; Dillip, Gowra Raghupathy; Pinto, Joana V.; Joo, Sang Woo; Martins, Rodrigo; Fortunato, Elvira
Abstract: Next‐generation electrical nanoimprinting of a polymeric data sheet based on charge trapping phenomena is reported here. Carbon nanoparticles (CNPs) (waste carbon product) are deployed into a polymeric matrix (polyaniline) (PANI) as a charge trapping layer. The data are recorded on the CNPs‐filled polyaniline device layer by "electro‐typing" under a voltage pulse (VET, from ±1 to ±7 V), which is applied to the device layer through a localized charge‐injection method. The core idea of this device is to make an electrical image through the charge trapping mechanism, which can be "read" further by the subsequent electrical mapping. The density of stored charges at the carbon–polyaniline layer, near the metal/polymer interface, is found to depend on the voltage amplitude, i.e., the number of injected charge carriers. The relaxation of the stored charges is studied by different probe voltages and for different devices, depending on the percolation of the CNPs into the PANI. The polymeric data sheet retains the recorded data for more than 6 h, which can be refreshed or erased at will. Also, a write–read–erase–read cycle is performed for the smallest "bit" of stored information through a single contact between the probe and the device layer. Abstract : Carbon nanoparticles (CNPs) are deployed into a polymeric matrix (polyaniline) as charge trapping sites, which function toward the concept of non‐destructive "electro‐typed" organic data‐storage devices. The dynamics of the localized electronic transport mechanism of a CNPs‐incorporated polyaniline (PANI) composite layer are demonstrated using atomic force microscopy.